(untitled) (Papeles, 2025)
The paper is part of the research project “Social assistance and training of social workers at the La Plata National University, 1905-1969”, which contributes to the knowledge of the regional and local particularities in which the profession emerges and, associated with it, as part of this process, the training and professional practice in certain institutions, mainly linked to the State. Likewise, recovering contributions from feminism, we propose to learn about aspects linked to the process of feminization of the assistance field as well as the diffusion of gender precepts in force at the time, attending to and analyzing their expressions in the training and performance of social workers. As part of this study, it is considered that an important analyzer to link the academic political project of the UNLP to the initial training of social workers (year 1938) are the first Study Plans of the career. In this sense, in this work we contextualize and analyze the changes between the 1938 and 1948 Study Plans of the Hygiene Visitors Career, identifying the theoretical-practical aspects that are transformed in the training, paying special attention to those linked to the feminization processes of the profession.